OPTIMALIZATION OF BREASTFEEDING TECHNIQUES USING “BREAST MODELS” - Suhaid, Dewi Novitasari; Margaretha Manungkalit, Eviyani; Kartiko Kusumo Wardani, Dyah Woro; Ida Pratiwi, Agustina; Leoni Irawan, Yetty; Kusmiyanti, Margaretha (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Exclusive breastfeeding is an attempt at enhancing the health and survival of infants during the initial 6 months of life. The World Health Organization (WHO) states that 2 out of 3 infants worldwide do not receive exclusive breastfeeding for the full 6 months. According to UNICEF, it is projected that by 2022, less than half (48%) of infants globally will be exclusively breastfed. The advantages of exclusive breastfeeding for infants encompass the acquisition of antibodies to prevent exposure to diseases, facilitation of brain and physical development, and mitigation of the risk of stunting. The successful practice of exclusive breastfeeding is profoundly affected by both intrinsic and extrinsic factors. Among the intrinsic factors that impact breastfeeding behavior, knowledge stands out. Insufficient or inaccurate information regarding the benefits of breastfeeding, the mechanism of milk production, as well as attachment and breastfeeding positions, are subjects that contribute to challenges in the breastfeeding process. Elevating awareness and comprehension of breast anatomy, milk production mechanisms, and proper attachment during breastfeeding among postpartum mothers will heighten self-efficacy concerning belief in behavioral change. Community service initiatives employ the health education approach utilizing a replica model of breast anatomy. The counseling sessions target parents (both husband and wife) undergoing postnatal health monitoring, and who are recipients of care in the postnatal care unit. The outcomes of this undertaking reveal a noteworthy 35% enhancement in participants' knowledge subsequent to receiving information on breast anatomy, milk production, and proper attachment."